2015
DOI: 10.1021/acs.langmuir.5b03081
|View full text |Cite
|
Sign up to set email alerts
|

Facile Algae-Derived Route to Biogenic Silver Nanoparticles: Synthesis, Antibacterial, and Photocatalytic Properties

Abstract: Biogenic synthesis of metal nanoparticles is of considerable interest, as it affords clean, biocompatible, nontoxic, and cost-effective fabrication. Driven by their ability to withstand variable extremes of environmental conditions, several microorganisms, notably bacteria and fungi, have been investigated in the never-ending search for optimal nanomaterial production platforms. Here, we present a hitherto unexplored algal platform featuring Chlorella pyrenoidosa, which offers a high degree of consistency in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 516 publications
(111 citation statements)
references
References 40 publications
2
107
0
2
Order By: Relevance
“…Recent reports in the literature have illustrated the bactericidal activity of silver nanoparticles (AgNPs; Rai et al, 2009; Aziz et al, 2015). Ingle et al (2008) have shown that AgNPs exhibited significant antimicrobial activity against Escherichia coli and multidrug resistant Staphylococcus aureus , while Pal et al (2007) have studied the impact of nanoparticle architecture on the antibacterial activity against E. coli .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports in the literature have illustrated the bactericidal activity of silver nanoparticles (AgNPs; Rai et al, 2009; Aziz et al, 2015). Ingle et al (2008) have shown that AgNPs exhibited significant antimicrobial activity against Escherichia coli and multidrug resistant Staphylococcus aureus , while Pal et al (2007) have studied the impact of nanoparticle architecture on the antibacterial activity against E. coli .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being eco-friendly, the emerging microbial synthesis route is also economical owing to significant reduction in downstream processing requirements. Inspired by the microbe’s ability to function under divergent extremes of temperature, pressure, and pH, several bacterial and algal chassis have been explored over the last decade by several groups, including our own laboratory (Nanda and Saravanan, 2009; Jain et al, 2011; Pantidos and Horsfall, 2014; Aziz et al, 2015; Patel et al, 2015). Notably, fungal-derived nanoparticle production shares these salient advantages and further combines facile scale up opportunities, economic viability, convenient processing and biomass handling, and faster biosynthesis rate in cell-free filtrate (due to the higher amount of proteins secreted in fungi with respect to bacteria) (Prasad et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Biological synthesis of silver nanoparticles by different microorganisms such as bacteria [23–26], fungi [7, 27]; algae [2830], plants [3134], actinomycetes [15, 20, 35] and myxobacteria [36] has been attempted by many researchers. Among these organisms, the synthesis of nanoparticles by actinobacteria has been less known [37].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum AgNPs synthesis was achieved after 90 min (Fig. 1D), and the reaction rate was more rapid than that reported in previous studies (Wei et al 2012;Das et al 2013;Ng et al 2013;Aziz et al 2015;Dhand et al 2016). …”
Section: Effect Of Reaction Timementioning
confidence: 43%